2015
DOI: 10.13075/ijomeh.1896.00311
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fatigue mats, low back pain, and electromyography: An interventional study

Abstract: Objectives: Increasing bilateral gluteus medius co-activation has been identified as one of the most important factors in developing low back pain due to prolonged standing in healthy people. This study aims to investigate the impact of an anti-fatigue mat on the bilateral gluteus medius co-activation pattern and to report the low back pain subjectively in 2 different standing positions on the normal rigid surface and on the anti-fatigue mat. Material and Methods: While carrying out an easy simulated professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 29 publications
1
37
1
7
Order By: Relevance
“…The increases in discomfort reported in this study over time are consistent with previous prolonged standing studies (Aghazadeh et al, 2015;Antle & Cote, 2013;Cham & Redfern, 2001;Kim & Stuart-Buttle, 1994;Coenen et al, 2017). The decreased lower back discomfort in the softer footwear mirrors the effects of softer flooring (Cham & Redfern, 2001;King, 2002;Lin et al, 2012;Orlando and King, 2004), suggesting that it could provide a similar benefit whilst being individual and portable.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The increases in discomfort reported in this study over time are consistent with previous prolonged standing studies (Aghazadeh et al, 2015;Antle & Cote, 2013;Cham & Redfern, 2001;Kim & Stuart-Buttle, 1994;Coenen et al, 2017). The decreased lower back discomfort in the softer footwear mirrors the effects of softer flooring (Cham & Redfern, 2001;King, 2002;Lin et al, 2012;Orlando and King, 2004), suggesting that it could provide a similar benefit whilst being individual and portable.…”
Section: Discussionsupporting
confidence: 88%
“…It has also been suggested that the low muscle contractions associated with prolonged standing are not ideal for recording spectral shifts (Cham & Redfern, 2001), possibly a result of the shifts being insensitive to low muscle contractions. The lack of difference between footwear for erector spinae co-contraction has been previously recorded between different flooring, despite increases in low back discomfort (Aghazadeh, et al, 2015). Muscle co-activation during standing can vary between individuals (Nelson-Wong & Callaghan, 2010), and it is feasible that fatigue in individual muscles could also be dependent on participant specific standing posture or pre-existing muscle preferences.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Javad Aghazadeh et al, (2015), investigated pain, while the participants stood on polyurethane foam 14.5 mm mat and concrete floor, using EMG & VAS. He concluded that anti-fatigue mat may be useful in reducing the low back pain although it objectively didn't significantly change the gluteus medius co-activation pattern related to the lower back pain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study suggests that anti fatigue mat and micro breaks should be provided to the workers to reduce muscle fatigue [03]. Aghazadeh, et al 2015, investigated pain, while the participants stood on polyurethane foam 14.5 mm mat and concrete floor, using EMG & VAS. He concluded that anti-fatigue mat may be useful in reducing the low back pain although it objectively didn't significantly change the gluteus medius co-activation pattern related to the lower back pain [04].…”
Section: Literature Reviewmentioning
confidence: 99%